2007
DOI: 10.1016/j.cognition.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Learning about occlusion: Initial assumptions and rapid adjustments

Abstract: We examined 6-month-olds abilities to represent occluded objects, using a corneal-reflection eye-tracking technique. Experiment 1 compared infants' ability to extrapolate the current pre-occlusion trajectory with their ability to base predictions on recent experiences of novel object motions. In the first condition infants performed at asymptote ($2/3 accurate predictions) from the first occlusion passage. In the second condition all infants initially failed to make accurate prediction. Performance, however, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 23 publications
9
51
0
Order By: Relevance
“…This conservative criterion of zero ensured that participants actually looked at the goal object before the PL hand has reached this goal. In other areas of research, for instance in studies of object representations, a more liberal criterion incorporating a 200 ms reaction time in anticipations has been used (e.g., Kochukhova and Gredebäck, 2007). We refrain from using the more liberal threshold as this is not in line with most prior action anticipation studies.…”
Section: Methodsmentioning
confidence: 99%
“…This conservative criterion of zero ensured that participants actually looked at the goal object before the PL hand has reached this goal. In other areas of research, for instance in studies of object representations, a more liberal criterion incorporating a 200 ms reaction time in anticipations has been used (e.g., Kochukhova and Gredebäck, 2007). We refrain from using the more liberal threshold as this is not in line with most prior action anticipation studies.…”
Section: Methodsmentioning
confidence: 99%
“…Habituation tasks yield a decrement of interest on repeated presentations of a single stimulus, even in neonates (Slater, 1995). Experiments investigating deferred imitation of behaviors have found that infants as young as 6 weeks imitated facial gestures (Meltzoff & Moore, 1994) and that 6-month-olds imitated actions demonstrated with a puppet (Barr, Dowden, & Hayne, 1996) and retained information about occluded objects (Kochukhova & Gredebäck, 2007) after a 24-h delay. In addition, 6-month-olds have been shown to imitate target actions viewed when they were 3 months of age, providing additional evidence for early functionality of neural substrates for long-term memory stores (Campanella & Rovee-Collier, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Third, by 6 months, infants begin to deal effectively with nonlinear trajectories, showing spatially accurate predictive eye movements when a target moves on a partly occluded circular (Gredebäck & von Hofsten, 2004) or angled path (Kochukhova & Gredebäck, 2007). In contrast, 4-month-olds construe nonlinear occlusion trajectories as discontinuous, and perception of continuity is disrupted when a linear object path is oriented diagonally relative to the occluder and background (Bremner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Infants can learn across trials to make appropriate predictive eye movements when observing inanimate objects move [13][14][15], and evidence of this learning has been found before they are able to perform objectdirected reaches [14,16]. Alternatively, and in line with assumptions about mechanisms underlying predictive eye movements towards object-directed actions [1,2,17], the mirror system may play a role.…”
Section: Discussionmentioning
confidence: 90%